Learning strategies during the covid-19 pandemic to improve Arabic skills - Ahmadi Ahmadi; Alin Hidayati; Alista Ajeng Prindyatno (Institut Studi Islam Muhammadiyah Pacitan, 2022)
This study aims to determine (1) types of Arabic learning strategies, (2) the effectiveness of learning strategies which can be applied in Arabic learning during covid-19 pandemic. This study is qualitative descriptive with secondary data sources. Data collection techniques are carried out through document studies through books, journals, website and other relevant sources. The results showed that (1) there are kinds of learning strategies that can be used to improve students’ Arabic skills during the covid-19 pandemic, there are: Intelligences-based classroom management and Mimicry memorization to improve Mufradat skills, flipped applications and mind mapping to improve Tarkib skills, whatsapp and youtube to improve istima' skills, Kallimni program and zoom application to improve Kalam skills, e-learning to improve Qira'ah skills, canva and google meeting applications to improve Kitabah skills, (2) the use of digital or online learning media is an effective leaning strategy used in learning Arabic during the covid-19 pandemic by adjusting the media to improve what Arabic skills needed